ChemInform Abstract: Cobalt‐Catalyzed Electrophilic Amination of Arylzincs with N‐Chloroamines. Issue 40 (12th September 2013) - Qian, Xin; Yu, Zailu; Auffrant, Audrey; Gosmini, Corinne
Abstract An efficient cobalt‐catalyzed electrophilic amination of arylzinc reagents with chloroamines is presented.